1972
DOI: 10.1136/jcp.25.7.590
|View full text |Cite
|
Sign up to set email alerts
|

Serum α-macroglobulins in renal disease and preeclampsia

Abstract: The serum levels of α2-macroglobulin and pregnancy-associated globulin (another α-macroglobulin) have been measured by means of a radial immunodiffusion technique in (1) renal disease with and without proteinuria, (2) in age- and sex-matched controls, (3) in preeclampsia with and without proteinuria, and (4) in normal pregnant controls. There are significant increases in α2-macroglobulin and pregnancy-associated globulin in renal disease accompanied by proteinuria but normal levels are found in renal disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Its action is very rapid, so that 'X2-macroglobulin inhibits only when large amounts of plasmin are generated.3 Concentrations of CX2-macroglobulin may be raised in the nephrotic syndrome. 4 In contrast, our study shows that OC2-antiplasmin may be deficient and that the low values seen attributable at least in part to renal loss. There are three possible consequences of this deficiency of a2-antiplasmin.…”
Section: Casecontrasting
confidence: 79%
See 1 more Smart Citation
“…Its action is very rapid, so that 'X2-macroglobulin inhibits only when large amounts of plasmin are generated.3 Concentrations of CX2-macroglobulin may be raised in the nephrotic syndrome. 4 In contrast, our study shows that OC2-antiplasmin may be deficient and that the low values seen attributable at least in part to renal loss. There are three possible consequences of this deficiency of a2-antiplasmin.…”
Section: Casecontrasting
confidence: 79%
“…Rupture of a popliteal cyst and acute rupture of the knee may occur in rheumatoid arthritis, and both may produce identical signs and symptoms. 4 In these patients the presence of a popliteal cyst noticed by the patients themselves and its subsequent disappearance suggests that the calf swelling was due to leakage from the cyst rather than rupture of the joint. What is not clear is why there was an associated pyogenic arthritis.…”
Section: Commentmentioning
confidence: 82%
“…Previous studies have reported that low levels of maternal plasma PZP are associated with spontaneous preterm birth (62) and an increased risk of preeclampsia (6365). On the other hand, opposing and inconclusive data have also been reported regarding a negative correlation between maternal plasma PZP levels and preeclampsia (66, 67).…”
Section: Discussionmentioning
confidence: 99%
“…A marked increase of PAG in sera and synovial fluids of patients suffering from RA seemed to be a new finding, though the increased serum PAG in patients with ma lignancy [1,3,4,6,7], liver cirrhosis [4] and renal diseases [4] has been already not ed. The increase of PAG in rheumatoid pa tients seemed to be closely related to their joint inflammation since a higher PAG level was found in the synovial fluids than in the paired serum samples and also the PAG level was related to the intensity of active arthritis of the patients.…”
Section: Discussionmentioning
confidence: 97%